2010
DOI: 10.3945/ajcn.2009.28443
|View full text |Cite
|
Sign up to set email alerts
|

Relation between estimates of cornstarch digestibility by the Englyst in vitro method and glycemic response, subjective appetite, and short-term food intake in young men

Abstract: The in vitro estimates of starch digestibility by the Englyst method predicted the effects of starch composition on blood glucose concentrations and FI in young men 30 and 120 min after consumption. This trial was registered at clinicaltrials.gov as NCT00980941 for experiment 1 and NCT00988689 for experiment 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 30 publications
4
60
0
Order By: Relevance
“…A study with pigs showed that the digestion of starch fractions in vitro was strongly associated with glucose occurrence in the portal vein in a similar experiment conducted in vivo and corrected for predicted gastric emptying (38). In a study with young human adults, the glycemic response to maltodextrin, whole grain, high-amylose, and regular corn starches was strongly correlated with in vitro estimates of their digestibility (3).…”
Section: Discussionmentioning
confidence: 95%
“…A study with pigs showed that the digestion of starch fractions in vitro was strongly associated with glucose occurrence in the portal vein in a similar experiment conducted in vivo and corrected for predicted gastric emptying (38). In a study with young human adults, the glycemic response to maltodextrin, whole grain, high-amylose, and regular corn starches was strongly correlated with in vitro estimates of their digestibility (3).…”
Section: Discussionmentioning
confidence: 95%
“…Four types of resistant starch exist: RS1-Physically inaccessible or indigestible starch, found in seeds, legumes, and unprocessed whole grains; RS2-Starch that occurs in its natural granular form, such as uncooked potato, green, banana flour, and high-amylose corn; RS3-Starch with digestion-resistant crystalline regions formed when starch-containing foods are cooked and cooled e.g. cooked-and-chilled potatoes or retrograded high-amylose corn; and RS4-Chemically modified starches not found in nature, including starch ethers, esters, and cross-bonded starches (Anderson et al 2010).…”
Section: Starch Properties Of Acha and Iburu Cereal Grainsmentioning
confidence: 99%
“…1o), total absorption (∑15-360 min) and ileal efflux (see Fig. 1h (Anderson et al 2010) demonstrated that the rapidly digestible starch in food is correlated with a higher blood glucose concentration at 30 min, but there was a lower glucose concentration 120 min after ingestion. It is also known that the insulin response is related to the amylose/ amylopectin ratio in meals (van Amelsvoort and Weststrate 1992) and one of the modifications described for Glycosade® is the higher quantity of amylopectin compared to traditional cornstarch (Correia et al 2008).…”
Section: Discussionmentioning
confidence: 91%